헤어살롱의 SNS 마케팅 특성이 브랜드 이미지와 정서적 유대감에 미치는 영향 - 강희선; Hee-sun Kang; 박은준; Eun-jun Park (한국미용학회지, 2023)
As the number of users and usage of SNS increases explosively, relationships with consumers and branding strategies in SNS marketing are becoming increasingly important for companies as well as consumers daily lives. This study examines the impact of hair salon SNS marketing characteristics on brand image and emotional bond. Based on previous research, a survey was conducted from October 30 to December 14, 2022, targeting 300 men and women in their 20s or older who use SNS in the Seoul and Gyeonggi regions. The conclusions based on the analysis results using SPSS 22.0 are as follows. As a result of this study, first, it was found that all sub-factors of SNS marketing characteristics (interactivity, playfulness, information provision, reliability) had a positive influence on brand image. Second, all sub-factors of SNS marketing characteristics (interactivity, playfulness, information provision, reliability) were found to have a positive influence on brand image. Third, brand image was found to have a positive influence on emotional bonding. Considering that the value and use of SNS is gradually increasing, if we understand the characteristics of SNS and recognize that the emotional bond formed through communication with consumers is an important factor, we can use long-term transaction-oriented marketing strategies and branding for competitive hair salons. It can be used to create a marketing strategy that creates differentiation.